Henoch-Schonlein purpura presenting sequentially as nodular rash, erythema nodosum, and palpable purpura - Kandan Balamurugesan; Stalin Viswanathan (Wolters Kluwer Medknow Publications, 2014)
We describe a 26-year-old woman who presented with a nodular rash on the elbows following an insect bite. Two days later, she developed erythema nodosum. Both these lesions were treated symptomatically. One week later, she had purpura, abdominal pain, hematuria, and arthralgias, following which steroids were administered. Her investigations revealed only microscopic hematuria that disappeared with therapy. This pattern of sequential appearance of rash and a nodular morphology are both unique features not previously reported.